PERAN K.H. DIMYATI DALAM PENYEBARAN ISLAM DI BARAN DESA PLOSO KECAMATAN SELOPURO KABUPATEN BLITAR 1950-1989 - qoidah, ulfatul; Rizal Zamzami (FIHROS: Jurnal Sejarah dan Budaya, 2024)
This research discusses the role of K.H. Dimyati in the spread of Islam in 1950-1989 in Baran, Ploso village, Selopuro subdistrict, Blitar district. K.H. Dimyati is a ulama figure who has influenced the pace of increasing understanding of Islam in the Baran community. This research aims to explain the biography and role of K.H. Dimyati in the spread of Islam in Baran, Ploso Village, Selopuro District, Blitar Regency. This research uses a historical research method which consists of four stages, namely heuristics, verification, interpretation and historiography by utilizing oral data sources through interviews and library sources. The results of this research are K.H. Dimyati, as a cleric who is descended from kiai, has a role in spreading Islam and attracting the religious awareness of the Baran people, especially with his high level of humanity, holding Al-Qur'an sorogans, teaching the yellow book, holding regular recitations specifically for the elderly and teaching kanuragan science. The influence of K.H. Dimyati can be seen from the people who still use the grave of K.H. Dimyati as a pilgrimage destination and sacred.